A program for comparing proteins using a graph representation of atom triplet surfaces - Eddeland, Daniel; Kvarfordt, Daniel; Weckstén, Mikael; Warg, Christofer; Lindskog, Hjalmar; Sellin, Joakim (My University, 2012)
This report details the development of software with the capability to find similarities on the surfaces of large biological molecules and display the result graphically in three dimensions. In the field of bioinformatics an approach to represent proteins as triangle surfaces has emerged and it is therefore interesting to have software tools available to examine this structure representation. The software has the ability to identify the largest common surface patch on two proteins as well as letting the user choose a patch to be matched for in the supplementary protein. This is done using an algorithm based on McGregor (1982) with some modifications. The result of the protein comparison is rendered in 3D with the option of rotating the proteins as well as changing several graphical options such as color and the visibility of wireframe and atoms. The resulting program works well for most inputs, but when comparing large, similar proteins the program can fail to terminate within an hour according to performance testing.
Keywords: Datavetenskap (datalogi); Computer Science